2014
DOI: 10.1016/j.jtcvs.2014.05.095
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary outcomes of complete atrioventricular septal defect repair: Analysis of the Society of Thoracic Surgeons Congenital Heart Surgery Database

Abstract: Objective Contemporary outcomes data for complete atrioventricular septal defect (CAVSD) repair are limited. We sought to describe early outcomes of CAVSD repair across a large multicenter cohort, and explore potential associations with patient characteristics, including age, weight, and genetic syndromes. Methods Patients in the Society of Thoracic Surgeons Congenital Heart Surgery Database having repair of CAVSD (2008–2011) were included. Preoperative, operative, and outcomes data were described. Univariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 20 publications
3
92
0
1
Order By: Relevance
“…In our population, neonates undergoing AVC surgery have a 33% prevalence of trisomy 21, which is less than the 78.4% prevalence noted by St. Louis and colleagues for all patients with AVSD [29]. However, our study focuses specifically on neonates; among those with AVSD having neonatal repair, trisomy 21 seems to be half as prevalent versus prior studies that include all age groups, likely due to differences in study populations in time to presentation for surgery.…”
Section: Commentmentioning
confidence: 61%
“…In our population, neonates undergoing AVC surgery have a 33% prevalence of trisomy 21, which is less than the 78.4% prevalence noted by St. Louis and colleagues for all patients with AVSD [29]. However, our study focuses specifically on neonates; among those with AVSD having neonatal repair, trisomy 21 seems to be half as prevalent versus prior studies that include all age groups, likely due to differences in study populations in time to presentation for surgery.…”
Section: Commentmentioning
confidence: 61%
“…Early surgical studies reported worse surgical outcomes in patients with Down syndrome undergoing repair for complete atrioventricular septal defect compared with patients without genetic syndromes . More recently, several studies have demonstrated equal or decreased risk of in‐hospital mortality for patients with Down syndrome undergoing repair of CHD (including complete atrioventricular septal defect) compared with patients with normal karyotypes except among patients with single ventricle physiology . Several studies that included long‐term outcomes for complete atrioventricular septal defect repair have demonstrated a decreased rate of reoperation for left atrioventricular valve repair and for subaortic stenosis in patients with Down syndrome, which is likely related to valve and left ventricular outflow tract morphology differences …”
Section: Genetic Architecture Of Chdmentioning
confidence: 99%
“…6 As crianças com SD e cardiopatia congé-nita passaram a ser operadas cada vez mais cedo, com resultados cirúrgicos e mortalidade sobreponíveis aos das crianças sem SD. 7,8 …”
Section: Introductionunclassified